Resonant Energy Transfer and Storage in Coupled Flow-Driven Heat Oscillators - Qian Ye; Stephen Sanders; Alessandro Alabastri (PRX Energy)
Oscillatory behavior in diffusive systems has recently attracted significant interest because of the possibility of extending the properties of resonators to transport phenomena. In this context, it is shown that internally heated and thermally coupled countercurrent flows display heat oscillations that are controllable by tuning the mutual rates at which such flows move. The combined effect of conduction and advection causes heat to circulate in the system, oscillating back and forth between the channels containing the flows. This oscillation allows heat in the system to be recycled, which is demonstrated to have practical applications, such as notably increasing the energy efficiency of solar-driven water desalination. In contrast to typical frequency-dependent oscillators, the resonance condition of flow-driven systems is determined by the fluid flow rates. While it is shown that a two-channel heat oscillator displays a resonance when the flow rates are equal and opposite, a complete understanding of these systems, especially when such heat oscillators are coupled and feature multiple channels, is still an open problem. Here, we investigate the fundamental properties of flow-driven resonant oscillators and introduce a figure of merit that completely quantifies the performance of coupled heat oscillators up to N-channel stacked configurations. Using this figure of merit, we determine the ideal configuration of flow rates to optimize a system with any number of channels. Interestingly, it is found that stacking multiple heat oscillators can increase the overall heat transfer for a fixed input power. The results of this work expand our fundamental understanding of flow-driven heat oscillators with implications for their application to real-world problems involving heat recovery, exchange, and accumulation.